Rates of adverse events in patients with ischemic stroke treated at thrombectomy capable hospitals. (26th May 2021) - Chaudhry, Saqib A; Sadaf, Humaira; Laleka, Ibrahim; Nasir, Wahid; Witzel, Catherine; Bahiru, Zelalem; Fang, Yun; Ishfaq, Fawad; Altaweel, Laith R; Qureshi, Adnan I
Abstract : Objective: To identify the beneficial effects of thrombectomy capable hospitals (TCHs), by comparing the incidence of in-hospital adverse events and discharge outcomes among patients with ischemic stroke treated at thrombectomy capable and non-thrombectomy capable hospitals in the United States. Methods: We used the data from the Nationwide Inpatient Sample from January 2012 to December 2017. Thrombectomy capable hospitals were identified based on the number of thrombectomy procedures performed by a hospital each year among patients with ischemic stroke. If a hospital performed 10 or more thrombectomy procedures, it was labelled a TCH. The inclusion criteria were age ≥18 years, and ischemic stroke (International Classification of Diseases 433 .x1-434.x1 (ICD-9) or I63 (ICD-10)) as primary discharge diagnosis. A comparative analysis of propensity-matched patient groups was done to study the influence of TCH admissions on in-hospital outcomes. Results: A total of 2 826 334 patients with primary ischemic stroke were identified. In a multivariate logistic regression model after adjusting for age, sex, race/ethnicity, hospital teaching status, comorbidities, and all patients refined diagnosis-related groups-based disease severity, patients admitted to a TCH were found to have low incidence of in-hospital adverse events: pneumonia (OR=0.86, 95% CI 0.78 to 0.93), urinary tract infection (OR=0.87, 95% CI 0.84 to 0.91), sepsis (OR=0.91, 95% CI 0.81 to 1.02), and pulmonary embolism (OR=0.89, 95% CI 0.77 to 1.03); in-hospital death (OR=0.82, 95% CI 0.78 to 0.88); and higher rate of home discharge (OR=1.09, 95% CI 1.06 to 1.12). Conclusions: A decrease in-hospital adverse events and improved discharge outcomes were observed among patients with ischemic stroke admitted to a TCH compared with a non-TCH.